Haruskah Plasenta Perkreta disertai Lakuna Bizarre? - Yusuf, Dwiyanarsi; Khonsa, Oni; Apriliawan, Tri; Lisnawati, Yuyun (Majalah Kedokteran Indonesia, 2019)
Background: Placenta percreta is a life-threatening condition that requires multidisciplinary management. The incidence of placenta percreta increases with increasing incidence of cesarean section. Antenatal diagnosis is an important point to prevent morbidity and mortality in both mother and baby. Ultrasonography (USG) is one of the relatively cheaper and easier modalities for diagnosing placenta percreta. Objective: To identify the optimal ultrasonographic criteria for the diagnosis of placenta percreta.Methods: We followed 2 cases, which performed antenatal care (ANC). Both patients then performed an ultrasound examination according to the placenta accrete index (PAI) method. The ultrasound assessment findings are then compared with intraoperative clinical findings and histological features. Results: From two cases, we did not find any Bizarre lacuna, but a thin retroplacental myometrial layer was found accompanied by loss of clear zone. The findings on ultrasonography are in accordance with intraoperative findings and histological features, where the appearance of the placenta percreta is clearly visible.Conclusion: It is different from the assessment of PAI, where the presence of lacuna is the biggest predictive factor for placenta adhesiva, in both cases, a thin myometrial layer of retroplacenta accompanied by a clear clear zone, although no lacuna was found, sufficiently describe the placenta percreta